The Role of Notch1 Signaling in Anaplastic Thyroid Carcinoma - Kim, Hyeon Jin; Kim, Min-Jung; Kim, Areumnuri; Jung, Chang Won; Park, Sunhoo; Koh, Jae Soo; Myung, Jae Kyung (Cancer research and treatment, 2017)
The Notch signaling pathway is widely expressed in normal, reactive, and neoplastic tissues; however, its role in thyroid tissues has not been fully elucidated. Therefore, this study was conducted to characterize the expression of the Notch signaling pathway in papillary thyroid cancer (PTC) cells and anaplastic thyroid cancer (ATC) cells. Expression of activated Notch1 in ATC and PTC paraffin-embedded tissues was determined by immunohistochemistry. The small interfering RNA techniquewas employed to knock down Notch1 expression in ATC and PTC cell lines. The expression of activated Notch1 was higher in ATC cases than in PTC cases. Inhibition of Notch1 significantly reduced proliferation and migration of ATC cells, but not PTC cells. In addition, inhibition of Notch1 in ATC cells significantly reduced the expression of key markers of epithelial-mesenchymal transition and cancer stem cells. Conversely, changes in the expression of these proteins were not observed in PTC cells. The results of this study suggest that Notch1 expression plays different roles in tumor progression in ATC and PTC cells. We also found that Notch1 expression was significantly related to the highly invasive or proliferative activity of ATC cells.